Crocodiles in captivity - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
The management of crocodiles in captivity by Melvin Bolton 1989 62pp, ISBN 92 5102875 3